Fever and laboratory profiles as predictors of serious bacterial infection in children - Ni Putu Veny Kartika Yantie; BNP Arhana; Purnomo Suryantoro (Paediatrica Indonesiana, 2012)
Background There is a debate on the use of high fever \\lith othermorbidities to predict serious bacterial infection (SBI). Bacterialinfection occurs in 3ô€‰15% of children with fever of 2: 39Â°C.Various laboratory parameters including increased Cô€‰reactiveprotein (CRP) levels, leukocyte counts, and absolute neutrophilcounts (AN C) have been studied for their usefulness in predictingthe occurrence of SBI, but with varied results. The ability todiscriminate whether a patient has a SBI can lead to improvedpatient management.Objective To evaluate fever of 2: 39Â°C, leukocyte counts of2: 15,000/mm3, ANC of 2: 1O,000/mm3 and CRP of 2: 10 mgiL aspredictors of SBI in children aged 1 monthô€‰ 18 years.Methods A caseô€‰controlled study was conducted by collectingdata from medical records at Sanglah Hospital, Denpasar. Subjectsin the case group were diagnosed \\lith SBls (bacterial meningitis,bacterial pneumonia, bacteremia or sepsis, urinary tract infections,or bacterial gastroenteritis), and subjects in the control group nonserious bacterial infections (nonô€‰SBI). Data was analyzed usingbivariate and multivariate methods \\lith 95% confidence intervalsand a statistical significance value ofP <0.05.Results Sixty subjects were studied, \\lith 30 subjects in the casegroup and 30 in the control group. Baseline characteristics ofsubjects were similar between the two groups. Fever and CRP werepredictors ofSBI [OR8.71 (95% CI 1.61 t046.98), P ô€€ 0.009; andOR 6.20 (95% CI 1.58 to 24.24), P ô€€ 0.012, respectively].Conclusion Fever 2: 39Â°C and CRP 2: 10 mgiL were significantpredictors of serious bacterial infections in children. [Paediatrrndones, 2012;52:313-6].